In ovo Peptide YY Administration and Jejunal Glucose Transport in Hatchling Turkey Poults:Effects of Dosage and Genotype - Coles, B.A.; Croom, J. (International Journal of Poultry Science, 2002)
Two trials were conducted to investigate the efficacy of in ovo administration of various dosages of peptide YY (PYY) on jejunal glucose absorption in hatchling poults from two strains of turkeys, Egg Line (EL) selected for egg production and British United Turkey (BUT) selected for growth. In both trials, either 100 µl saline (1.025% w/v) or saline plus PYY were injected into the air cell of fertile EL and BUT line eggs at day 25 of incubation. At hatch, poults were euthanized by cervical dislocation, the jejunum removed and its weight and unstretched length recorded. Two to 4 mg cross-sections of the mid-jejunum were used to estimate active and passive glucose absorption using the accumulation of 3-O-methy-D-glucose (3OMG) in the presence and absence of phlorizin. In Trial 1, EL and BUT eggs were administered saline or saline plus 600 µg/kg egg wt, while in Trial 2, EL and BUT eggs were administered either saline or saline plus 300, 600, or 900 µg/kg egg wt. No differences were observed in hatchling body weights of poults from saline and PYY treated eggs from either line in both trials. In Trial 1, poults from EL treated eggs (600 µg/kg egg wt) had greater active jejunal 3OMG uptake compared with saline treated controls (332 vs. 270 pmol/min/mg tissue, p